A preliminary feasibility study for pentachlorophenol column sorption by almond shell residues - B. N. Estevinho (2008)
Almond shells, by-products from the northern region of Portugal, were used for the adsorption of pentachlorophenol (PCP) from aqueous solutions. The use of almond shells, as agricultural waste products, may present several economical advantages, considering that 50% (in mass) of almonds are constituted by shells. No research has been conducted concerning their use as sorbent without previous activation treatment. Besides performing column adsorption experiments, this study also focus on the structural and chemical characterization of the almond shells, as a way to understand the nature of sorption. Scanning electron microscopy (SEM), mercury porosimetry and Fourier transform infrared spectroscopy (FTIR) were techniques used, in addition to chemical analysis. PCP determinations in aqueous media were performed by gas chromatography with electron capture detector (GC/ECD) after sample extraction and clean-up using solid-phase microextraction (SPME). Results proved that almond shells have a high affinity for PCP sorption, with removal efficiencies higher than 99.98%, where column experiments made PCP concentration decrease from 10mg/L to values lower than the legal limit (1 mu g/L). Column experiments with 5 and 10g of sorbent (respectively 2.9 and 5.8 cm bed height), were passed with acidified PCP solutions (pH 2) at a flow rate of 4 mL/min, until saturation was achieved after 28 and 41 h. An adsorption capacity of 6322 mg/L was estimated using BDST model, which proved that the almond shells confirm to be an encouraging sorbent for cheap water remediation solutions.